Apartheid et capitalisme : le système économique de l'Afrique du Sud - Johnstone, Frederick; Legassick, Martin; Wolpe, Harold; Morris, Mike; Messiant, Christine; Meunier, Roger (Paris : Maspero, 1979)
Bibliotheek François Vercammen
Frans
Monografie